Assessing and improving edge roughness in pad-printing by using outlines in a one-step exposure process for the printing form - Bodenstein, Christina; Sauer, Hans Martin; Fernandes, Felipe; Dörsam, Edgar (Journal of Print and Media Technology Research, 2023)
We describe the specificities of the pad-printing form production. In printing experiments, we show the influence of different printing forms, in dependence on raster frequency and printing form material, on the printing quality of pad-printed patterns. A typical defect in pad-printing, the ‘stamp effect’, which occurs as a wavy contour, was determined and traced to the printing form production. By incorporating so-called outlines into the printing form, we were able to reproduce patterns with an edge roughness of less than 3 µm. We provide descriptions of the implementation of these outlines. To measure and analyze the edge roughness and edge defects we developed an image-based method to quantitatively assess the quality of edge patterns. With the use of outlines in the printing form, it seems feasible to use pad-printing for source and drain contact manufacturing on printed thin film transistors. Thus, the reproduction of electrically conductive, interdigital patterns for sources and drains having an electrode distance of less than 10 µm appears possible.